Myopia. Part II – prevention and treatment of the latest guidelines - Oleszczyńska-Prost, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Myopia is a refractive error to progress as a child matures. It is, therefore, important to prevent further progression. There are several methods for myopia prevention and treatment. One of the most effective approaches involves orthokeratology alongside medical treatment. Other important preventive factors are duration and quality of near work, orthoptic and accommodation exercises, accurate prescription, daylight exposure, diet and lifestyle. There are also reports of potential stem cell treatments.